2013
DOI: 10.1186/1745-9974-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cineole in patients suffering from acute bronchitis: a placebo-controlled double-blind trial

Abstract: ObjectiveCineole has mucolytic, bronchodilating and anti-inflammatory properties and reduces the exacerbation rate in patients suffering from COPD, as well as ameliorates symptoms in patients suffering from asthma and rhinosinusitis. Based on these effects, we therefore postulated the hypothesis that patients with acute bronchitis would also benefit from therapy with Cineole.MethodsAs part of a double-blind, placebo-controlled, multi-center-study, a total of 242 patients with confirmed acute bronchitis was ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 13 publications
(12 reference statements)
5
40
0
2
Order By: Relevance
“…However, there are still various side eff ects of the locally applied glucocorticoids [ 13 , 18 , 19 ] . Actually, in a double-blind, placebo-controlled, multi-centerstudy in patients with acute bronchitis 1,8-cineole signifi cantly improved the Bronchitis Sum Score and particularly cough frequency at day 4 [ 20 ] . Apart from proving effi cacy in the treatment of bronchitis and sinusitis [ 4 -6 , 21 ] , 1,8-cineole as concomitant therapy has also demonstrated an ability to reduce exacerbations in COPD as well to improve lung function and health condition in asthma in randomized controlled clinical trials [ 22 -25 ] .…”
mentioning
confidence: 97%
“…However, there are still various side eff ects of the locally applied glucocorticoids [ 13 , 18 , 19 ] . Actually, in a double-blind, placebo-controlled, multi-centerstudy in patients with acute bronchitis 1,8-cineole signifi cantly improved the Bronchitis Sum Score and particularly cough frequency at day 4 [ 20 ] . Apart from proving effi cacy in the treatment of bronchitis and sinusitis [ 4 -6 , 21 ] , 1,8-cineole as concomitant therapy has also demonstrated an ability to reduce exacerbations in COPD as well to improve lung function and health condition in asthma in randomized controlled clinical trials [ 22 -25 ] .…”
mentioning
confidence: 97%
“…A randomized study in acute bronchitis (n = 242) with 1,8-cineole over 10 days showed significant improvements after 4 days of the bronchitis severity-sum score compared to placebo [15]. Concomitant therapy with 1,8-cineole (two capsules of 100 mg three times daily) was also studied in a placebo-controlled study (n = 242) in COPD (Global Initiative for Chronic Obstructive Lung Disease (GOLD) II-III) with a primary outcome of reduction of exacerbations, and a secondary outcome of changes in lung function, respiratory symptoms and quality of life scores during 6 months [16].…”
Section: Approved Efficacy Of 18-cineole In Randomized Placebo-contmentioning
confidence: 99%
“…It is also evident that acute bronchitis symptoms usually occur after an upper respiratory tract infection [35]. Only 50 % of patients with acute bronchitis produce purulent sputum that represents detritus containing tracheobronchial epithelial and inflammatory cells [36] as well as mucus. As the cough is often not 'wet' but 'dry', mucolytic agents are not always helpful.…”
Section: The Debatementioning
confidence: 99%